2013
DOI: 10.12681/mms.413
|View full text |Cite
|
Sign up to set email alerts
|

Marine litter from circalittoral and deeper bottoms off the Maltese islands (Central Mediterranean)

Abstract: During the 2005 leg of the MEDITS trawl survey, benthic anthropogenic debris around the Maltese Islands (central Mediterranean) was quantified for the first time, with the aim of studying its abundance and distribution in the area. 357 items were sampled from 3.5 km 2 of swept area. Each item was recorded, measured and its planar and surface areas were estimated. Plastic (47%), metal and glass (13% each) were the most prevalent types of litter in terms of number. Limestone slabs, sacks and fabric were the item… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…Litter abundance on these submarine features was patchy, with high and low densities of litter reported within each ocean. However, all litter abundances were within those previously reported in the North Atlantic Ocean for seamounts, banks, mounds and ridges (Pham et al, 2014) and for coastal waters (Galgani et al, 2000;Mifsud et al, 2013), but greater than that previously observed in more remote locations (Antarctic Peninsula and Scotia Arc; Barnes et al, 2009). Different methodologies, including sampling techniques, may account for some of the differences observed, as Barnes et al (2009) collected data by trawl rather than video systems such as employed in this current study, but could also reflect the more remote areas surveyed by Barnes et al (2009).…”
Section: Distribution and Abundancesupporting
confidence: 85%
See 1 more Smart Citation
“…Litter abundance on these submarine features was patchy, with high and low densities of litter reported within each ocean. However, all litter abundances were within those previously reported in the North Atlantic Ocean for seamounts, banks, mounds and ridges (Pham et al, 2014) and for coastal waters (Galgani et al, 2000;Mifsud et al, 2013), but greater than that previously observed in more remote locations (Antarctic Peninsula and Scotia Arc; Barnes et al, 2009). Different methodologies, including sampling techniques, may account for some of the differences observed, as Barnes et al (2009) collected data by trawl rather than video systems such as employed in this current study, but could also reflect the more remote areas surveyed by Barnes et al (2009).…”
Section: Distribution and Abundancesupporting
confidence: 85%
“…Strandline litter and accumulation of debris in surface water are well-reported in the media, and citizens actively monitor and lobby about these issues. The issue of the un-seen benthic litter has recently attracted more attention (Galgani et al, 2000;Barnes et al, 2009;Mifsud et al, 2013;Schlining et al, 2013;Pham et al, 2014;Woodall et al, 2014). This current study is the first of its kind to assess litter on numerous deep-sea raised topological features, using the same techniques including the same observer, in two oceans with different local anthropogenic activities.…”
Section: Resultsmentioning
confidence: 99%
“…Iñiguez et al 2016) in the Ligurian and northern Tyrrhenian Sea (e.g. Serena et al 2011), the waters around Malta (Mifsud et al 2013, Pace et al 2007, the Strait of Sicily (Fiorentino et al 2015), the northern Adriatic Sea (Strafella et al 2015, Pasquini et al 2016, Melli et al 2017 and the Aegean Sea (e.g. Stefatos et al 1999, Ioakeimidis et al 2014.…”
Section: Discussionmentioning
confidence: 99%
“…The most distinctive features of these bathyal layers [38] are the presence of huge scattered hard grounds produced by “deep water white corals” (madrepores, mainly Lopheliapertusa Linnaeus, 1758, and Madrepora oculata Linnaeus, 1758 [39]), and the piling up, year after year, of thousands of limestone slabs, which are used as anchors for Fish Aggregating Devices (FADs) in the fishery of dolphin fish ( Coryphaena hippurus Linnaeus, 1758). These slabs make extended surfaces on the grounds, between 300 m and 800 m, which make the seabed unsuitable for trawling activities, or even untrawlable altogether [40,41]. …”
Section: Methodsmentioning
confidence: 99%